1989
DOI: 10.1111/j.2044-8295.1989.tb02309.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 72 hours of sleep loss on psychological variables

Abstract: A study was conducted on the effects of 72 hours of sleep loss and modified continuous operations on performance and psychological variables. This paper presents the results of self-report data of 12 subjects for the following psychological variables: sleepiness, affect, motivation, cognitive difficulties, and waking dreams. The relationship between the self-report measures and performance in a visual search and memory task is also examined. Most of the psychological variables are significantly affected by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 13 publications
2
23
0
2
Order By: Relevance
“…For our subjects, the most demanding hours with respect to alertness were in the early morning. The same has been reported in previous studies as well (Babkoff et al, 1991;Mikulincer et al, 1989).…”
Section: Discussionsupporting
confidence: 78%
“…For our subjects, the most demanding hours with respect to alertness were in the early morning. The same has been reported in previous studies as well (Babkoff et al, 1991;Mikulincer et al, 1989).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, strong circadian oscillations are observed throughout the entire TSD period. Diverse studies have found these same results (Angus et al, 1985;Brendel et al, 1990;Dinges et al, 1997;McCann et al, 1992McCann et al, , 1993Mikulincer et al, 1989;Wilhelm, Wilhelm, Ludtke, Streicher, & Adler, 1998). An increase in sleepiness, such as we found, is common among normal subjects following sleep deprivation, as well as among depressive subjects, while not being related to the sleep-deprivation antidepressant effect.…”
Section: The Effect Of Sleep Deprivationsupporting
confidence: 53%
“…Habitually, decreases in activation, vigor, and vigilance, and increases in fatigue, sleepiness, anxiety, confusion/daze, irritability, and other signs of increasing disturbances following sleep deprivation have been reported (Brendel et al, 1990;Cutler & Cohen, 1979;Dinges et al, 1997;Gillberg & Akerstedt, 1981;Hill, Welch, & Godfrey, 1996;Mikulincer, Babkoff, Caspy, & Sing, 1989;Reynolds et al, 1986). In any case, the majority of these studies tend to conclude with a report concerning the global effect of sleep deprivation on these variables.…”
mentioning
confidence: 86%
“…Por ejemplo, la comparación del sueño de los jóvenes de 1963 con los de 1910-1911 mostraba una reducción del tiempo total de sueño de aproximadamente una hora y media, lo que sugiere que tendemos a perder horas de sueño por el actual estilo de vida (Carskadon, 1993). Por otra parte, diversos estudios han señalado los efectos perjudiciales de la privación de sueño en diversas medidas del estado de ánimo (Blagrove y Akehurst, 2001;Brendel et al, 1990;Beutler, Cano, Miró y Buela-Casal, 2003;Cano, Miró y Buela-Casal, 2001;Cutler y Cohén, 1979;Gillberg y Akerstedt, 1981;Hill et al, 1996;Mikulincer et al, 1989;Miró, Cano, Espinosa y Buela-Casal, 2002b;Reynolds et ai, 1986).…”
Section: -Profundidad Del Sueño Discusiónunclassified
“…Generalmente estos estudios coinciden en señalar que este tipo de manipulaciones del sueño suelen producir efectos perjudiciales en un amplio rango de variables asociadas al bienestar psicológico. Por ejemplo, la privación de sueño produce generalmente un decremento en activación, vigor y vigilancia y un incremento en fatiga, somnolencia, ansiedad, confusión e irritabilidad (Brendel et al, 1990;Cutler y Cohén, 1979;Gillberg y Akerstedt, 1981;Hill, Welch y Godfrey, 1996;Leproult et al, 2003;Mikulincer, Babkoff, Caspy y Sing, 1989;Miró, Cano y Buela-Casal, 2002a;Reynolds etal., 1986).…”
Section: Introductionunclassified